Incidence and fertility status of hydatid cysts in buffaloes - Sheeba, A.; Sangaran, A.; Latha, B.R.; Raja, A. (Buffalo Bulletin, 2016)
Study on the incidence of hydatidosis in food animals meant for human consumption such as buffaloes was done at the time of slaughter by inspecting the carcasses and viscera for the presence of hydatid cysts with particular reference to lungs, liver, spleen etc., Based on the observation, the incidence of hydatid cysts in buffaloes examined was found to be 11.11 percent. With regard to the organ wise involvement, the presence of hydatid cysts was more in lungs, followed by liver and the fertility rate of hydatid cysts was high in lungs.